Does vancomycin resistance increase mortality in Enterococcus faecium bacteraemia after orthotopic liver transplantation?: a retrospective study - Dubler, Simon; Lenz, Martin Philipp; Zimmermann, Stefan; Richter, Daniel; Weiss, Karl Heinz; Mehrabi, Arianeb; Mieth, Markus; Bruckner, Thomas; Weigand, Markus A.; Brenner, Thorsten; Heininger, Alexandra (Antimicrobial resistance and infection control, 2020)
The relevance of vancomycin resistance in enterococcal blood stream infections (BSI) is still controversial. Aim of this study was to outline the effect of vancomycin resistance of Enterococcus faecium on the outcome of patients with BSI after orthotopic liver transplantation (OLT).
Gesehen am 31.03.2020